Profile and risk factors of blood donors who experienced adverse reactions: a cross-sectional study on donor hemovigilance data reported to the national network from 2020 to 2022 in China - Yang, Junhong; Zhu, Wenqin; Xie, Dongfu; Xu, Qing; Guo, Xiaojie; Zeng, Jia; Xu, Yongzhu; Huang, Xia (Frontiers in Public Health, 2025)
BackgroundWhile international cooperation in blood donor safety surveillance is growing, data from China’s national network remains unpublished. We have established a national donor hemovigilance system to collect data and analyze the current state of blood donor safety in China.Materials and methodsWe conducted a cross-sectional study on donor hemovigilance data reported to the national network from 2020 to 2022 in China. Demographic information and data on adverse donor reactions (ADRs) among blood donors were collected from 85 Blood Services. R software (version 4.2.3) was used for all statistical analyses. Frequency and composition rates were used to describe the data of total donation, as well as data on the different types of ADRs. The Chi-square test was used to analyze risk factors for Vasovagal reactions (VVRs) and inter-group comparisons of VVRs stratified by age (18–22; 23–29; 30–39; 40–49; 50–60), gender (female/male), donation history (first time/repeat), and blood donation volume (200 mL/300 mL/400 mL), type of collection site (fixed site/blood collection shelter/blood collection vehicle/others) and donor source (individual/social group/high school). Lastly, risk factors for blood donation-related syncope were explored.ResultsBetween 2020 and 2022, 32,523 cases of ADRs were reported, among which VVRs accounted for 96.8% of all reactions. The overall reported incidence of ADRs was 12.577%. Notably, the incidence of VVRs decreased with increasing donor age. Additionally, the estimated incidences of VVRs were higher among female donors (13.600%) and first-time donors (18.536%) compared to male donors (11.205%) or repeat donors (5.819%). Moreover, 1,120 VVRs with syncope were recorded, accounting for 3.56% of total VVR cases. Finally, donors from outdoor blood collection sites (0.590%) and groups (1.073%) were at a significantly higher risk of syncope compared to those from indoor blood donation sites (0.438%) and individual donors (0.174%).ConclusionThe reported incidence rate of ADRs related to blood donation was very low. The higher prevalence of VVR and syncope in young, females, first-time donors, college students, and donating in mobile vehicles.